The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1590/s0103-84782004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Abertura floral de Dendranthema grandiflora Tzvelev. ´Bronze Repin´após rmazenamento a frio seguido de “pulsing”

Abstract: 63Abertura floral de Dendranthema grandiflora Tzvelev. 'Bronze Repin' após armazenamento a frio seguido de "pulsing".Ciência Rural, v. 34, n. 1, jan-fev, 2004. Ciência Rural, Santa Maria, v.34, n.1, p.63-70, jan-fev, 2004 ISSN Abertura floral de Dendranthema grandiflora Tzvelev. ´Bronze Repin´após rmazenamento a frio seguido de "pulsing" INTRODUÇÃOO abastecimento contínuo e com qualidade deve ser uma preocupação constante dos produtores de flores durante todas as fases do processo produtivo. Os pequenos p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
3
4
0
4
Order By: Relevance
“…We observed that the opening point of central inflorescence partially open (Figure 1b, 1c, 1g) qualifies visually the aesthetics of the floral stem of safflower, allowing its commercialization by a greater period in virtue of the greatest number of inflorescences open with the passage of the days, without damage to the durability of the same, as verified in Table 2. Bellé et al (2004) reported that the point of floral opening or of harvest is the stage in which the flower can be completed with its collocation only in water, since that the plant presents good reservations and conditions of adequate temperature, corroborating with the results of this work. Castro et al (2014) and Cordeiro et al (2011) verified that calla lily (Zantedeschia aethiopica (L.) Spreng.)…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We observed that the opening point of central inflorescence partially open (Figure 1b, 1c, 1g) qualifies visually the aesthetics of the floral stem of safflower, allowing its commercialization by a greater period in virtue of the greatest number of inflorescences open with the passage of the days, without damage to the durability of the same, as verified in Table 2. Bellé et al (2004) reported that the point of floral opening or of harvest is the stage in which the flower can be completed with its collocation only in water, since that the plant presents good reservations and conditions of adequate temperature, corroborating with the results of this work. Castro et al (2014) and Cordeiro et al (2011) verified that calla lily (Zantedeschia aethiopica (L.) Spreng.)…”
Section: Resultssupporting
confidence: 87%
“…The withering and yellowing of the leaves, in general, began after nine days of preservation, and it was accentuated from 15 days, period that also the senescence of the central inflorescences of floral stem of safflower intensified, presenting score three (Figure 3) of quality scale aforementioned. Evidences of senescence similar to the one of this work were verified by Bellé et al (2004) for chrysanthemum from 10 days of preservation postharvest in different solutions and, Sanches et al (2017) verified evidences of senescence of calla lily from 8 days of preservation in solutions for floral opening. In relation to the efficiency of the preservative solutions, we observed that the mass loss of floral stems of safflower preserved in solution of distilled water + sucrose 2% was the one that obtained the greatest acceleration of deterioration in comparison to the other ones, reaching loss on average of 46% at six days of preservation for all the seasons.…”
Section: Resultssupporting
confidence: 83%
“…Among the tested temperatures for chrysanthemum Ono ', 1.5°C best preserved flowers (Vieira and Brigida, 2009). While Vieira and Lima (2009) found that there was no increase in longevity of chrysanthemum Faroe when stored at 10°C for 48 h. Belle et al (2004) ascertained that storage at low temperatures delayed the onset of symptoms of senescence in Dendranthema grandiflora subjected to 2°C. Kelley et al (2003), working with edible flowers, found that Viola tricolor L. cv.…”
Section: Coolingmentioning
confidence: 94%
“…As soluções conservantes para flores obedecem, basicamente, a uma composição que permite fornecer energia às flores ou bloquear o desenvolvimento microbiano, ou a síntese de etileno (Bellé et al 2004). O uso de sacarose, em solução pós-colheita, vem sendo recomendado por autores como Carneiro et al (2002) e Barbosa et al (2006).…”
Section: Key-wordsunclassified